2021
DOI: 10.1186/s13099-021-00407-7
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between severities of COVID-19 and the gut microbiome: implications of bacterial co-infections?

Abstract: COVID-19 is an acute respiratory distress syndrome and is often accompanied by gastrointestinal symptoms. The SARS-CoV-2 has been traced not only in nasopharyngeal and mid-nasal swabs but also in stool and rectal swabs of COVID-19 patients. The gut microbiota is important for an effective immune response as it ensures that unfavorable immune reactions in lungs and other vital organs are regulated. The human gut-lung microbiota interplay provides a framework for therapies in the treatment and management of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 61 publications
2
40
0
2
Order By: Relevance
“…Thus, the administration of probiotics may function through several signaling pathways, resulting in the prevention and treatment of various pathological conditions [ 63 ]. As microbiome dysbiosis is linked with the severity of COVID-19, the implication of probiotics in modulating the severity has been suggested as a promising weapon against COVID-19 [ 24 , 25 , 64 ]. Several studies focusing on the gut microbiome and probiotics in COVID-19 have been conducted, and several registered clinical trials have focused on the usage of probiotics in COVID-19 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the administration of probiotics may function through several signaling pathways, resulting in the prevention and treatment of various pathological conditions [ 63 ]. As microbiome dysbiosis is linked with the severity of COVID-19, the implication of probiotics in modulating the severity has been suggested as a promising weapon against COVID-19 [ 24 , 25 , 64 ]. Several studies focusing on the gut microbiome and probiotics in COVID-19 have been conducted, and several registered clinical trials have focused on the usage of probiotics in COVID-19 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have shown that COVID-19 is often associated with altered gut microbiota composition, reflecting disease severity [20][21][22][23] . As growing evidence indicates the interaction between COVID-19 and host-microbiota homeostasis, researchers have been investigating the potential of manipulating gut microbiota with probiotics to enhance the host immune system 24, 25 . The current review summarizes important findings on the direct association between SARS-CoV-2 infection and the gut-lung axis in addition to the pathological effects of dysbiosis on COVID-19 severity.…”
Section: Reviewmentioning
confidence: 99%
“…Given that SARS-CoV-2 has receptors in the intestinal endothelium, infection will reduce the expression of ACE2 in the gastrointestinal tract, and thus by various mechanisms may lead to intestinal dysbiosis [ 138 ]. The number of ACE-2 receptors in the duodenum increases with age, which suggests a potential entry mechanism for SARS-CoV-2 [ 139 ] and effects on its infectiousness and the severity of COVID-19 [ 140 , 141 ]. Research has detected the SARS-CoV-2 virus in anal swabs and stool samples in nearly 50% of patients with COVID-19, which suggests that the digestive tract may be an extrapulmonary site of replication and activity of the virus [ 6 , 142 ].…”
Section: Food Components With Regard To Their Protective Effects In Covid-19 Patientsmentioning
confidence: 99%
“…However, there is a concern about the possibility of opportunistic pathogen infections, especially in people with comorbidities such as cancer, leaky gut syndrome, or diabetes, and in organ transplant recipients [ 152 ]. Some probiotic strains take advantage of weakened immunity to transform into opportunistic pathogens, causing acute pneumonia, endocarditis, or sepsis [ 141 ]. There is a need for studies encompassing the effects of both diet and probiotics on the severity of COVID-19.…”
Section: Food Components With Regard To Their Protective Effects In Covid-19 Patientsmentioning
confidence: 99%
“…However, this imbalance in the intestinal microbiome can be associated with an increased severity of the disease in COVID-19 patients [ 42 ]. One of the responsible mechanisms could be the alteration in the microbiota with the contribution of defensive bacteria including Klebsiella, Streptococcus spp., and Ruminococcus gnavus that are associated with over-secretion of pro-inflammatory cytokines and exacerbation of the cytokine storm in infected patients [ 43 ].…”
Section: Glp-1 Sars-cov-2 and The Gut Microbiotamentioning
confidence: 99%